Diterpenes in espresso coffee: impact of preparation parameters - Marzieh Moeenfard (2015)
The aim of the present study was to evaluate the effect of preparation conditions of espresso coffee (EC) on the diterpenes profile. ECs were prepared from roasted and ground (R&G) Arabica coffee and analyzed for the content of cafestol and kahweol by liquid-liquid extraction followed by HPLC-DAD, as well as their lipid content. The main variables in the present study were as follows: the water quantity, the amount of coffee, the particle size, the percolation time, the water temperature and pressure. Average cafestol, kahweol and lipid content of R&G Arabica coffee were 467 ± 20 mg/100 g, 638 ± 33 mg/100 g and 15.1 ± 0.1 g/100 g, respectively. Although all parameters influenced the diterpenes content of ECs (21 samples), the particle size and water quantity were the most significant ones. It was possible to reduce the total diterpenes from 58.8 ± 0.7 mg/L (2.3 mg/40 mL) to 30.7 ± 0.8 mg/L (1.2 mg/40 mL) by varying the brewing conditions. The average extraction yield of diterpenes and lipids was in the range of 1.5-2.5 and 7.0-9.0 %, respectively. Regarding total cafestol and kahweol, very fine particles seem to be more desirable for the production of highly concentrated brew (2.3 mg/40 mL) with cafestol and kahweol extraction yields of 2.8 and 2.9 %, respectively, than other studied ECs. On the other hand, samples brewed at 70 °C exhibited lower diterpenes content (1.2 mg/40 mL) and diterpenes extraction efficiency (1.4 %) with respect to all other considered parameters. This study clearly shows that parameters for coffee brew preparation may be changed to modify the diterpenes content of ECs according to the desired purpose.